SIG PERSEBARAN TENAGA KESEHATAN MENURUT KECAMATAN DI KOTA MALANG TAHUN 2019-2021 - Septiani Eka Retnosari; Bambang Agus Herlambang, Ahmad Khoirul Anam (CV. ADIBA AISHA AMIRA, 2024)
According to WHO (2006) Health workers contribute up to 80% in Health Development. Determining the development of Health human resources (SDMK) as one of the priorities because Indonesia is still facing manpower problems, both in terms of number, type, quality and distribution. The HRK ratio per 100,000 population has not yet met the target set (WHO, 2011). This research aims to determine the picture of the HRK situation in Malang City, East Java from 2019 to 2021. The results of the research show that the number of HRK is as follows: the number of doctors is 5,121, midwives are 2,301, nurses are 9,761, public health workers are 112, environmental health workers are 165, There are 1,527 pharmaceutical workers, 496 nutrition workers and 687 medical laboratory technology experts. In conclusion, the highest number of human resources in Malang City, East Java in 2019-2021 are doctors and nurses. Equal distribution of human resources has not yet occurred, health human resources are more abundant in big cities while they tend to be fewer in other cities. The HRK ratio in 2019-2021 is still below the Minister of Health's Decree target even though there are several types of HRK that are close to the target. It is hoped that the relevant agencies can optimize efforts to equalize health human resources (SDMK) in districts/cities so that their distribution can be even, which is expected to improve health services for the community.